HUBUNGAN TIPE OLAHRAGA DENGAN NILAI VO2 MAX PADA ATLET PELATDA PROVINSI NTB - Siti Ruqayyah; Dian Rahadianti (Nusantara Hasana Journal, 2022)
A good quality of physical fitness is a necessity for every human being which can be obtained by exercising regularly. One element of physical condition that is very important in sports is cardiovascular endurance or often referred to as the maximum oxygen volume uptake (VO2 Max). Types of sports can be divided into 2, athletics and non-athletic. Athletics is a sport that consists of a combination of several types of physical exercise, such as running, javelin throwing, high jumping, while non-athletic groups are sports such as sand volleyball, rock climbing, and futsal. The purpose of this study was to determine the relationship between the type of sports and the value VO2 Max in the Pelatda Athletes of West Nusa Tenggara Province (NTB). This research is analytic observational using a cross sectional research design. The total population in this study were athletes from various sports at Pelatda of NTB. The sampling technique used was total sampling. In this study, the chi square test was used. The sample in this study amounted to 39 athletes consisting of an athletic sports group of 13 athletes and a non-athletic sports group of 26 athletes. The value of VO2 Max in the good category was found to be 61.53% in the non-athletic group and 23.08% for the athletic group. The results showed that there was a relationship between the type of sport and the VO2 Max value.